An assessment of empathy levels of dental students’ in Nepal: A cross-sectional comparative study - Ghimire, Siddharth; Dixit, Punam Basnet; Roy, Deepak Kumar; Dhital, Shweta; Dahal, Sirjana (Journal of Kathmandu Medical College, 2020)
Background: Empathy is a behavioural aspect of understanding and communicating with a desire to help. Empathy in medical personnel with patient is one of the basic ingredients of good physician/dentist –patient relationships.Objectives: To assess empathy level among dental undergraduate students, interns and dental postgraduate students of Nepal and to investigate the differences in empathy scores based on gender and year of dental training.Methodology: A cross-sectional questionnaire study was carried out among 240 dental students of different dental colleges in Nepal. Eighty students were included in each group of third to final-year undergraduate dental students, interns and postgraduate students. Data was collected using a standard-validated, self-administered Jefferson Scale of Empathy-Health Care Provider Student Version (JSE-HPS). This questionnaire included 20 items with a seven-point Likert scale. This scale has relevant content that allows assessing empathy between students and their patients. The collected data was entered in Microsoft Excel and statistical analysis was done in Statistical Package for the Social Sciences version 20.Results: Out of 240 dental students, 74 (30.8%) were males and 166 (69.2%) were females with the mean age of 25.35 ±3.203. The mean empathy score was 79.59 ± 6.492.There was no significant difference in mean empathy level score by gender. The interns were the most empathetic (80.80 ± 6.147). The mean empathy score was found to be highest for the students with less than one year of experience of treating patient (81.85 ± 7.841).Conclusion: Empathy should be given importance to in dental curriculum to improve dentist-patient relationship, thereby improving the treatment outcomes.